2008
DOI: 10.1177/0265407507087959
|View full text |Cite
|
Sign up to set email alerts
|

Positive marital illusions and culture: American and Turkish spouses' perceptions of their marriages

Abstract: This study investigated the degree to which positive illusions about one's spouse and marriage are a universal feature of human cognitions about marriage or are culturally moderated. Positive marital illusions were compared across three samples (49 American spouses, 58 Turkish spouses in nonconsanguineous marriages, and 56 Turkish spouses in consanguineous marriages). Positive illusions were assessed by comparing positive and negative trait ratings of the spouse and the generalized other. The positive trait ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…In contrast, the Japanese sample revealed evidence of relationship effacement, in which scores on the negative aspects of one's own partner and romantic relationship were higher than scores for the average person and average relationship. Fowers, Fisiloglu, and Procacci (2008) examined differences in idealization among the following three groups: American married individuals and Turkish individuals either from consanguineous (''marriages between members of the same extended family,'' p. 271) or from nonconsanguineous marriages. Contrary to Endo et al (2000), Fowers, Fisiloglu, et al found a cultural difference when participants were asked to rate their partner on positive aspects.…”
Section: Links To Established Social-cognitive Theoriesmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast, the Japanese sample revealed evidence of relationship effacement, in which scores on the negative aspects of one's own partner and romantic relationship were higher than scores for the average person and average relationship. Fowers, Fisiloglu, and Procacci (2008) examined differences in idealization among the following three groups: American married individuals and Turkish individuals either from consanguineous (''marriages between members of the same extended family,'' p. 271) or from nonconsanguineous marriages. Contrary to Endo et al (2000), Fowers, Fisiloglu, et al found a cultural difference when participants were asked to rate their partner on positive aspects.…”
Section: Links To Established Social-cognitive Theoriesmentioning
confidence: 99%
“…Instruments that assess personality or personal attributes are commonly used to generate self-ratings and partner ratings (e.g., Murray & Holmes, 1997, 1999Neff & Karney, 2002). Another way to obtain difference scores is to compare individuals' reports of their partners and/or relationships with their reports of average or ideal partners and/or relationships (e.g., Endo et al, 2000;Fowers, Fisiloglu, et al, 2008). As Fowers, Veingrad, et al (2002) have correctly noted, ''there is no gold standard for assessing a relationship that captures an unambiguous reality against which a partner's perception of the relationship could be evaluated to assess 'distortion''' (p. 450).…”
Section: Measurement Issuesmentioning
confidence: 99%
See 3 more Smart Citations